ENSAIOS DE CONTROLE DE NEMATÓIDES EM CANA-DE-AÇÚCAR, COM ALDICARB - Roccia, Antonio O.; Lordello, Luiz Gonzaga E.; Lordello, Rubens R. A. (REVISTA DE AGRICULTURA, 2015)
ENSAIOS DE CONTROLE DE NEMATÓIDES EM CANA-DE-AÇÚCAR, COM ALDICARB